Stress distributions of infinite strip steel reinforced elastomeric isolators with a rubber core. (15th June 2023) - Noggle, Rose; Van Engelen, Niel C.
Highlights: Analytical solution for elastomeric isolators with a rubber core is derived. Twenty-one FEA bearing models are considered to validate the analytical model. Validation is conducted based on the compression and bending modulus and normal and shear stress distributions. Trends related to the size of the rubber core are identified. The analytical model is valid for isolators with up to 75% of the reinforcement width removed to accommodate the rubber core. Abstract: Lead-rubber bearings contain a lead core that provides an advantageous increase in initial stiffness and increased energy dissipation during earthquake events. Despite these advantages, the inclusion of the lead core is an environmental and health concern and can be costly. The use of rubber cores in lieu of lead cores has been proposed as an alternative and shown to achieve excellent energy dissipation. The inclusion of the rubber core also decreases the weight of the isolator through the partial removal of the steel reinforcement or the replacement of lead with a lighter material. In this paper, the inclusion of a rubber core in an infinite strip steel-reinforced elastomeric isolator was investigated. An analytical solution was developed based on the assumptions of the pressure solution including and excluding the compressibility of the elastomer for the compression and bending properties. Finite element analysis was subsequently conducted to verify the analytical solution. The analysis considered three different shape factors and a rubber core up to 90% of the width of the isolator. The models were used to determine the elastic moduli as well as the normal and shear stress distributions under pure bending and rotation. The verified analytical solution is an important tool for designers.